Hydrodynamic investigation of polysaccharides and their interaction with casein - Morris, Gordon Alistair (2001)
Polysaccharide systems (pectin, carrageenan, guar, locust bean gum, xanthan and xylan) have been characterised using a variety of hydrodynamic techniques including sedimentation velocity, sedimentation equilibrium, size exclusion chromatography - multi-angle laser light scattering (SEC-MALLS), and viscometry. Results suggest that the polysaccharides selected are, in general, rigid or semi-rigid molecules with a large hydrated volume, this is important in relation to polysaccharide structure - function relationships. In addition the effect of incorporating a UV absorbing substituent group was also investigated for two pectin samples and an arabinoxylan polysaccharide, the reaction conditions result in beta-elimination of the pectin chain in one case, but there was no significant effect on the other pectin or arabinoxylan. The effect of increased temperature was also investigated with respect to high and low methoxy pectins, this resulted in beta-elimination of high methoxy pectin and a mild conformational change in low methoxy pectin.